DAMPAK JUDI ONLINE TERHADAP KELUARGA NELAYAN DI PULAU BAAI KOTA BENGKULU - Sari, Racma Duicta; Heriyanti, Lesti (JURNAL ILMIAH IDEA, 2025)
This study aims to explore the impact of online gambling on the economy of fishermen's families on Baai Island, Kampung Melayu District, Bengkulu City. Indonesia, as a maritime country, has many coastal areas inhabited by fishermen. However, with advances in technology and increasingly easy internet access, people's habits have begun to change, including the increasing practice of online gambling. This phenomenon not only occurs in big cities, but also reaches coastal areas such as Kampung Melayu. This study uses a qualitative approach with a descriptive method. Data were collected through in-depth interviews with heads of fishermen's families, wives, and children involved in online gambling, as well as direct observation. research shows that online gambling has a negative impact on the economy of fishermen's families. Many families experience financial difficulties due to family members who are addicted to online gambling, which threatens the sustainability of their livelihoods. The results of the study revealed that online gambling not only harms the individuals involved, but also has an impact on the economic welfare of the family. Addiction to online gambling causes the allocation of time and money that should be used for family needs to be used for gambling. In addition, psychological stress, such as depression and loss of hope, is also experienced by individuals who are trapped in online gambling. This study is expected to provide insight into the socio-economic impacts of online gambling in coastal areas, as well as suggest increasing public awareness and empowering family economies as solutions to reduce these negative impacts.